Analisis Hukum terhadap Penetapan Kasus Pelecehan Seksual di Bekasi Menurut Kitab Undang-Undang Hukum Pidana - Aditia Widya Tama (Referendum : Jurnal Hukum Perdata dan Pidana, 2024)
This study analyzes the legal application in determining cases of sexual harassment in Bekasi under the Indonesian Penal Code (KUHP), given the high prevalence of such cases in the region. Using descriptive-analytical methods and statutory and conceptual approaches, the research identifies how criminal law is applied in addressing sexual harassment, challenges in investigation processes, and Islamic law perspectives on this phenomenon. The data includes primary, secondary, and tertiary legal materials obtained through literature studies. The findings reveal that while the KUHP provides sufficient provisions for handling sexual harassment cases, its implementation faces significant challenges, including limited legal awareness, social stigma, and lack of evidence. The study highlights the need for a more comprehensive approach to addressing these cases, including regulatory reforms supporting justice for victims and stricter sanctions for perpetrators. In conclusion, strengthening criminal law and raising legal awareness are essential to improving the effectiveness of law enforcement in sexual harassment cases in Indonesia.